The Influence English Language Difficulties on Learning Outcomes among Children: A Case Study of State Junior High School Tanjung Morawa - Fadillah, Putri; Putri, Rini Fadhillah; Sari, Siti Mayang (Institut Agama Islam Sunan Giri Ponorogo, 2023)
In Indonesia, English is a foreign language to be studied both at school institutions and not. In practice students and teachers still face many obstacles in the learning process, especially in English proficiency. Various responses can be found in class related to these problems, especially on students' language difficulties, students' attitudes during the learning process. With these problems student learning outcomes, and participation in carrying out learning activities and groups are less effective. So that in conversation material students have not shown maximum seriousness and learning outcomes. This study aims to describe the difficulties faced by students in learning English and the causal factors related to student conversations. This study used a qualitative approach with interview instruments, journal literature, and analyzing student learning outcomes. Analysis of research data was carried out in three ways, namely interviews, reviewing journals, drawing conclusions and verifying student learning outcomes. The results showed that the research subjects had difficulty learning English in various conversation materials. This occurs as a result of different levels of English mastery and learning outcomes according to assessment standards.